An Analysis of Finance and Banking Development to Indonesia Economic Growth (Montly Production Index): VECM - Febrianti, Ika Rahma; Hakim, Lukman; Rahayu, Siti Aisyah Tri (Advances in Social Sciences Research Journal, 2023)
Sustainability of finance growth is supported by a good finance system. Finance inovasion eases user with more efficient service. Referring to some economic literatures, it has been found that there are different perspectives between the relationships of finance development and economic growth. In responding to that phenomena, this research aims to investigate the influence of the total credit from conventional banks, the total credit of micro small dan medium enterprises, the amount of debit or ATM transaction and the amount of electronic transaction to the Indonesia electronic growth either in a short term or in a long term. The data that is used in this research are monthly time series from January 2015 to March 2022 by using sample from 87 months. The used method is qualitative descriptive by using Vector Error Correction Model and the result shows that in a long term, total credit from conventional bank has a significant impact for the economic growth, while the transaction amount through ATM/debit tends to have negative impact for the economic growth. Independent variables are significant and able to explain the dependent variables as much as 68% and the remaining 32% are influenced by other variables that are not used in this research.